AB1150-HPR Preference for Etanercept Pen versus Syringe in Patients with Chronic Arthritis. Nursing Educational Workshop. (10th June 2014) - Garcia-Diaz, S.; Girabent-Farres, M.; Roig-Vilaseca, D.; Reina-Sanz, D.; Cerdà-Gabaroi, D.; Gonzalez, M.; Torrente-Segarra, V.; Fíguls, R.; Corominas, H.
Abstract : Background: Etanercept is an anti-TNF biological therapy, which is available in either a prefilled syringe or a pen myclic. Nursing staff plays an important role in the administration and monitoring of this drug, helping patients with chronic inflammatory diseases to reach self-management. The use of Etanercept in pen form rather than syringe prompted this study within our hospital. Objectives: The aims of this study were to evaluate the level of fear of post-injection pain prior to the administration, the difficulty in handling the device, and the level of satisfaction of patients using a pre-filled syringe versus an Etanercept pen, as well as to evaluate the usefulness of the training given by nursing staff prior to starting with the pen, and the preferences of patients after using both devices. Methods: A prospective study was designed to follow-up a cohort of patients during a six months period. The data was collected using questionnaires developed for this purpose. The study was placed at the Consorci Sanitari Integral, Moises Broggi Hospital, Barcelona. All the patients were using prefilled syringe at the beginning of the study and changed into a pen during the study. The first phase (October '11), consisted of a theoretical-practical workshop where the new pen was presented, explained and patients practiced how to use it; a questionnaire was then completed. Afterwards (in November-December '11), all patients were given the pen. In January, March and May 2012, these patients were asked to complete a new questionnaire. The data was analyzed with SPSS 18.00. Rank and McNemar tests were performed. Statistical significance was pre-set at an alpha level of 0.05. Results: A total of 29 patients were included, of whom 69% female, and with a mean age 52.5±10.9 years. Of these, 48% had rheumatoid arthritis, 28% psoriatic arthritis, 21% ankylosing spondylitis, and 3% undifferentiated spondyloarthropathy. There were no statistically significant differences either with the fear or pain or handling of the device between the syringe and the pen (p=0.469; p=0.812; p=0.169 respectively). At six months, 59% of patients referred to being satisfied or very satisfied with the pen. Almost all (93%) found useful or very useful the training given by nursing staff prior to using the pen, and 55% preferred the pen over the pre-filled syringe (see Table 1 ). Conclusions: The etanercept pen is another subcutaneous device option for patients with chronic arthritis and this was preferred by the majority of patients. According to the present study, nursing educational workshops before starting this therapy would be recommended. References: Barra L et al (2009). Carmona et al (2002). O'Neill&Silman (1994). Braun J et al (1998). Fleischmann&Iqbal (2007). Kivitz A et al (2006). Van Eijk-Hustings Y et al (2012). Acknowledgements: Catalina Padilla, Jesus Esteve, Aroa Rodriguez and all the patients who participated in the study Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2351